Evaluation of GaN and InGaN semiconductors as potentiometric anion selective electrodes - Dimitrova, Rozalina Stefanova (My University, 2006)
Ion selective electrodes (ISEs) are chemical sensors primarily used for in situ analysis and monitoring of air, water, and land. Despite their easy fabrication, low cost, and simple usage, ISEs still suffer from the sensitivity of their response to temperature variations, solution turbidity, interferences from other ions in solution, drift of the electrode potential, membrane fouling, and short lifetime. As a result, investigating new materials to develop ISEs that can address some of these limitations is a worthwhile and challenging topic of research. The excellent mechanical, thermal and chemical stability of gallium nitride (GaN) and indium gallium nitride (InGaN) semiconductors, coupled with their resistance to corrosion and low toxicity if dissolved, are some of the properties that make these materials prime candidates for a variety of sensor applications, particularly at high temperatures and in harsh environments. This thesis evaluates the potential of these two semiconductor materials for replacing conventional ISE membranes with a solid-state semiconductor surface/solution interface. The benefits gained from this novel design of the ISE sensing element are assessed.
Keywords: Electrodes, Ion selective; Indium gallium nitride; Gallium nitride